2017
DOI: 10.1007/s00213-017-4575-z
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin-3/RXFP3 signalling in mouse hypothalamus: no effect of RXFP3 activation on corticosterone, despite reduced presynaptic excitatory input onto paraventricular CRH neurons in vitro

Abstract: Relaxin-3/RXFP3 signalling is proposed to be involved in the neuromodulatory control of arousal- and stress-related neural circuits. Furthermore, previous studies in rats have led to the proposal that relaxin-3/RXFP3 signalling is associated with activation of the hypothalamic-pituitary-adrenal axis, but direct evidence for RXFP3-related actions on the activity of hypothalamic corticotropin-releasing hormone (CRH) neurons is lacking. In this study, we investigated characteristics of the relaxin-3/RXFP3 system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…Although RXFP3 has been shown to modulate synaptic inputs to parvocellular PVN CRF neurons ( C. Zhang et al, 2017 ) and neurons of the bed nucleus of stria terminalis in mice ( Ch'ng et al, 2019 ), neither RLN3 nor a selective RXFP3 agonist influenced excitatory NMDA/AMPA or inhibitory GABA A receptor-mediated postsynaptic currents (spontaneous and miniature) recorded from PVN MNCs in our rat brain preparations. We therefore conclude that RLN3 inputs primarily act on postsynaptically located RXFP3 to modulate MNC activity in the rat.…”
Section: Discussionmentioning
confidence: 78%
“…Although RXFP3 has been shown to modulate synaptic inputs to parvocellular PVN CRF neurons ( C. Zhang et al, 2017 ) and neurons of the bed nucleus of stria terminalis in mice ( Ch'ng et al, 2019 ), neither RLN3 nor a selective RXFP3 agonist influenced excitatory NMDA/AMPA or inhibitory GABA A receptor-mediated postsynaptic currents (spontaneous and miniature) recorded from PVN MNCs in our rat brain preparations. We therefore conclude that RLN3 inputs primarily act on postsynaptically located RXFP3 to modulate MNC activity in the rat.…”
Section: Discussionmentioning
confidence: 78%
“…1 www.gtexportal.org/home/gene/RXFP3 Furthermore, several rodent studies have observed that relaxin-3 can influence the hypothalamic-pituitary adrenal and gonadal axes, although some of these effects may be due to relaxin-3 binding to RXFP1, rather than RXFP3 (Zhang et al, 2017;De Ávila et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of the functions of this receptor has uncovered that RXFP3 might play a vital role in several aging-related disorders, as a connection has been found to several hallmarks of aging, such as oxidative stress and DNA damage response [24], similarly to the aging keystone GIT2 [6,7]. In addition, research by other groups has elucidated possible roles for RXFP3 in stress responses [25], anxiety [26], depression [26,27], feeding [15,[28][29][30], arousal [28], and alcohol addiction [31]. Given the plethora of possible physiological activities of RXFP3, we will next assess how RXFP3 functionality may intersect with several of the classical hallmark processes involved with the aging process (Figure 1).…”
Section: Aging and Aging-related Disordersmentioning
confidence: 99%